Respostas comportamentais do boto-vermelho (Inia geoffrensis) ao turismo de interação no baixo Rio Negro, Amazonas - Nunes, Angélica Cristina Gouveia (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
Acoustic variations in animal vocalizations may carry codifications of motivation, which in social species may improve communication among and between groups. The Amazon river dolphin, or boto, are considered acoustically quiet animals, but are capable of producing may sounds. The behavioral contexts and functions of these vocalizations are still unclear, as well as the species vocal repertoire. The goals of this study were to describe the botos vocal repertoire and verify if vocalizations corresponds to specific behavioral contexts. Acoustic recordings and behavioral observations were made in three different floatinghouses were in-water interactions with these animals occur, in the lower Negro river region, between May to August 2014. In these sites, wild boto aggregations are formed due to offer of fish. Each site has different animals, that are recognized by marks and scarring patterns. Simple and robust acoustic parameters were measured and analyzed through acoustic softwares. Acoustic variables did not differ among the three sites, but did significantly varied among behavioral contexts. The peak frequency at the fundamental (PFF) and max frequency (MF) in aggressive behavioral contexts were much lower than in other contexts. The vocal repertoire of this species is compound of gradations and transitions and are occasionally difficult to separate into discrete call types. Botos changed their behavior due to interactions with humans and the use of supplementary feeding. At the oldest location of interaction, the probability of animals to stay in aggressive behavior increased. Animals remain close to the floating most of the time. This might be due to the sensitisation to supplementary feeding. Botos have been conditioned to human contact due to the use of supplementary feeding as a means of attraction. We suggest management measures to ensure the quality of tourism and animal welfare.
Keywords: Boto-vermelho; Inia geoffrensis; Bioacústica